Perancangan Sistem Pemantauan dan Pengontrolan Truk Pada PT X - Robert Yunior Anthoni; Benedictus Rahardjo (Jurnal Titra, 2021)
PT X is an automotive company that operates as a manufacturer, assembler, and distributor in and outside the country. PT X is a subsidiary of a multinational company. PT X uses the Just In Time (JIT) principle, so it does not have inventory (zero inventory). PT X produces motorbikes that have a type and color type, where motorbikes produced will be distributed to 29 main dealers. Land distribution will use trucks provided by the transporters, where the trucks used will be regulated in accordance with government regulations. The regulation issued by the government regarding this matter is the rule of Over Dimension Overload (ODOL), where the regulation regulates the dimensions of the trucks used to transport goods. The use of dashboards is a solution to simplify the process of monitoring and controlling the condition of each truck at each main dealer. The use of dashboards for monitoring and control processes is more effective and efficient, because the dashboard can provide a lot of information through just one view. The use of the dashboard increases the progress of improvement, where in January 2019 only 63.13% to 76.55% in April 2019.